High-strength battery cell housing for large circular battery cells made from aluminum alloy

By using aluminum alloy to manufacture the shell of large cylindrical battery cells, the problems of insufficient strength and thermal management in the prior art are solved, and efficient thermal management and weight optimization are achieved.

JP2025508619APending Publication Date: 2025-03-28HYDRO ALUMINIUM ROLLED PRODUCTS GMBH
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024536233
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-17
Filing Date
2022-12-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high strength and good thermal management in large cylindrical battery cells, and there is also the problem of excessive weight.

Method used

The shell of a cylindrical battery cell is made of aluminum alloy, and the tensile strength and electrical conductivity are improved by adjusting the composition and heat treatment state of the aluminum alloy to achieve higher thermal management and weight optimization.

Benefits of technology

High strength and good thermal management of large cylindrical battery cells are achieved, while reducing weight and maintaining high efficiency of battery capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025508619000001_ABST
    Figure 2025508619000001_ABST
Patent Text Reader

Abstract

The present invention relates to a battery cell housing for a circular battery cell, comprising a cylindrical housing shell having an outer diameter of more than 15 mm, preferably more than 20 mm, particularly preferably more than 22 mm, and to the use of an aluminum alloy for manufacturing the battery cell housing according to the invention. The object of providing a high-strength battery cell housing for a circular battery cell having a cylindrical housing shell having a diameter of more than 15 mm, preferably more than 20 mm, particularly more than 22 mm, which allows for improving the properties in terms of thermal management and weight of the circular battery cell, without unduly limiting the capacity of the circular battery cell, is to provide a high-strength battery cell housing for a circular battery cell, comprising a cylindrical housing shell having a diameter of more than 15 mm, preferably more than 20 mm, particularly more than 22 mm, which housing shell at least partially consists of an aluminum alloy, and which has a yield strength R p0.2 is at least 183 MPa, preferably at least 220 MPa, particularly preferably at least 250 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a battery cell housing for a circular battery cell comprising a cylindrical housing shell having an outer diameter larger than 15 mm, preferably larger than 20 mm, particularly preferably larger than 22 mm, and to the use of an aluminum alloy for manufacturing the battery cell housing according to the invention. [Background technology]

[0002] Battery cells are used in a wide variety of technical applications to supply electrical loads with electrical energy. Fields of application for battery cells are, for example, in electric mobility, in particular electric cars, electric bicycles and electric scooters, in consumer electronics, in particular laptop computers, tablet computers, mobile phones, digital cameras and camcorders, or in energy technology, in particular battery storage, to name just a few. To form a battery module, i.e. a battery system, several battery cells are often connected in series or parallel. However, there are also applications in which a single battery cell is used as the energy source.

[0003] Battery cells can be fundamentally differentiated into primary batteries, which can only be discharged once and cannot be repeatedly charged, and secondary batteries, which can be repeatedly charged. The necessary electrochemical processes providing the functionality of a battery cell can be implemented with a wide variety of different materials, both in primary and secondary batteries. Examples of primary batteries in this context are alkaline-manganese batteries, zinc-carbon batteries, nickel-oxyhydroxide batteries or lithium-iron sulfide batteries, to name just a few. Examples of secondary batteries are lithium-ion batteries, sodium-ion batteries, nickel-cadmium batteries, nickel-metal hydride batteries or nickel-zinc batteries, to name just a few.

[0004] For many years, lithium-ion secondary batteries have been increasingly used, especially in the field of electric mobility and consumer electronics, due to their relatively high gravimetric and volumetric energy density. Like other types of battery cells, lithium-ion secondary batteries have a battery cell housing, which forms the external shape of the battery cell and encloses a cavity that contains, among other things, the anode material, the cathode material, the separator and the electrolyte. A distinction may be made between different designs of battery cell housings. A cylindrical battery cell housing has essentially the shape of a cylinder. If the height of the cylinder is greater than the diameter, it is called a circular battery, otherwise a button battery. A battery cell housing of prismatic design has essentially the shape of a prism, in particular a rectangular parallelepiped. Another variant is the pouch design, where the battery cell housing essentially has the shape of a pocket or pouch.

[0005] Due to the high requirements for strength and mechanical stability as well as for electrochemical stability associated with the electrolyte acting corrosively on the battery cell housing, up to now especially cylindrical battery cell housings have been largely manufactured from nickel-plated steel. The predominant circular battery cell type is the type 18650 circular battery cell with a diameter of 18 mm. In various applications these are being replaced by type 21700 21 mm circular battery cells. Furthermore, for example in the field of electric mobility, the replacement of type 21700 circular battery cells by type 46800 circular battery cells with a diameter of 46 mm is already foreseen. The increasing number of these cell types places increasing demands on the removal of heat generated inside these circular battery cells and therefore on the electrical and thermal conductivity of these battery cell housings.

[0006] A battery pack having a large number of circular battery cells also requires contributions from the circular battery cells to the mechanical design of the battery pack to achieve weight reduction.

[0007] The use of aluminum alloys for cylindrical battery cell housings is already known, but only for the aluminum alloy AA 3003. For example, a battery cell housing having an outer diameter of 13.8 mm and a height of 49.0 mm is known from US Pat. No. 5,399,323. This battery cell housing was manufactured by deep drawing and stretch drawing from a round segment of aluminum alloy sheet made of aluminum alloy type AA 3003.

[0008] For battery cell housings with smaller cross-sectional areas, the mechanical stability of the battery cell housing is essentially a result of the rigidity of its geometry as a cylinder, but for larger cross-sectional areas of circular battery cells above an outer diameter of 15 mm, the yield strength R of the material of the battery cell housing p0.2 With regard to mechanical strength, nickel-plated steel, known per se as a material for battery cell housings, is considered as the standard in this context. Nickel-plated steel strip of type AISI 1020 has a typical yield strength R of 350 MPa. p0.2 is assumed.

[0009] The reference material steel still offers the smallest wall thickness in an increasing number of battery types and therefore the largest possible volume to accommodate the electrode windings, or so-called "jelly rolls", which consist of a multi-layer structure of anode material, separator layers and cathode material, wound on a winding core and placed inside the battery cell housing. It determines the energy capacity of a circular battery cell.

[0010] Battery cell types with diameters larger than 15 mm are placing ever-increasing demands on the removal of heat generated inside the battery cell housing. Steel does not offer an optimal solution in this situation. Furthermore, there are also weaknesses due to the weight of circular battery cells made of steel when used in electric mobility, which is, however, an important factor for the realization of battery-powered electric drives in electric mobility. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] U.S. Patent No. 6,258,480(B1) Summary of the Invention [Means for solving the problem]

[0012] Based on this, it is an object of the present invention to provide a high-strength battery cell housing for a circular battery cell having a cylindrical housing shell with a diameter larger than 15 mm, preferably larger than 20 mm, in particular larger than 22 mm, which allows for improved properties in terms of thermal management and weight of the circular battery cell, without unduly limiting the capacity of the circular battery cell.Furthermore, it is intended to provide a use of an aluminum alloy for manufacturing the battery cell housing.

[0013] The above object is to provide a battery cell housing, the housing shell being at least partially made of an aluminum alloy, and the yield strength R p0.2 is at least 183 MPa, preferably at least 220 MPa, particularly preferably at least 250 MPa.

[0014] According to the invention, a housing shell at least partially made of an aluminum alloy means a housing shell made of an aluminum alloy and which may have further features, for example an external or internal coating, which are not critical for the mechanical strength of the housing shell.

[0015] According to the study, the material is at least partially made of an aluminum alloy and has a yield strength R of at least 183 MPa. p0.2Specifying that a typical internal pressure stability of 9 MPa is met for a large circular battery cell, e.g., type 4680, having a diameter of 46 mm, a housing shell for a circular battery cell having a wall thickness that allows a "jelly roll" winding length of the circular battery cell to be less than 5% shorter compared to a housing shell made of steel of type AISI 1020. A winding core diameter of 4 mm was assumed in these studies.

[0016] At the same time, the significantly higher electrical and thermal conductivity of the aluminum alloy of the housing shell compared to steel ensures a significantly improved overall heat dissipation from the interior of the circular battery cell. With the higher yield strength of the housing shell, for example at 258 MPa, the winding length reduction of the aforementioned "jelly roll" is actually less than 2%. Furthermore, due to this significantly higher density of steel, circular battery cell housings made of aluminum alloys have significant weight advantages. These are indeed significant, for example at a yield strength R of 258 MPa. p0.2 For a housing shell having a .DELTA..times..times.2.times.

[0017] According to a first configuration of the battery cell housing, the housing shell of the battery cell housing has a wall thickness that satisfies the following relationship: outer diameter / wall thickness of the circular battery cell>41.5, preferably>47.5, particularly preferably>55.0. The higher the ratio of outer diameter to wall thickness of the housing shell, the lower the drop in the interior volume of the housing shell for a "jelly roll" winding length that is proportional to the capacity of the battery cell, and the proportionally lower the weight of the battery cell housing. Thus, the gravimetric energy density, together with the low density of aluminum, can be significantly improved by reducing the wall thickness.

[0018] The electrical conductivity of aluminum alloys is significantly higher than that of steel, even 23 MS / m for the AA3003 aluminum alloy. According to a further configuration, the housing shell preferably has an electrical conductivity higher than 25 MS / m, preferably higher than 28 MS / m, particularly preferably higher than 30 MS / m. The electrical conductivity naturally depends on the alloy composition of the aluminum alloy and also on the microstructural state. Low-alloy AlMgSi alloys, which are hardenable and can be transformed into one of the states T6, T6x, T7 or T7x by solution annealing followed by artificial ageing, have a combination of particularly high electrical conductivity and very high strength. On the other hand, steel of type AISI 1020 has an electrical conductivity of about 6.3 MS / m, which is less than one-quarter of the highest electrical conductivity of aluminum alloys. It is expected that the performance of a secondary battery with a battery cell housing according to the invention will be improved when charging and discharging the battery, since the ohmic resistance of the cell is reduced and the thermal conduction in the cell housing is improved.

[0019] According to one configuration, the aluminum alloy of the housing shell of the battery cell housing comprises, by weight percent: 0.2%≦Si≦2.0%, preferably 0.2%≦Si≦1.5% or 0.2%≦Si≦1.3%, Fe≦0.5%, Cu≦0.8%, preferably ≦0.6%, more preferably ≦0.45% Mn≦1.4%, preferably 1.0%≦Mn≦1.4%, more preferably Mn≦0.6%, Mg≦2.0%, preferably ≦1.5%, more preferably 0.2%≦Mg≦1.5% Cr≦0.25%, preferably ≦0.15%, Zn≦0.4%, preferably ≦0.25%, Ti≦0.2%, preferably 0.01%≦Ti≦0.20%, V≦0.05%, preferably ≦0.03%, more preferably ≦0.0015%, Zr≦0.25%, preferably ≦0.20%, more preferably ≦0.05% or ≦0.0015%, Ni≦0.2%, preferably ≦0.05%, more preferably ≦0.03% or ≦0.0015%, The balance is Al and incidental impurities of not more than 0.05% individually and not more than 0.15% in total. The composition is

[0020] When combined with the specified amounts of iron and manganese contents, a silicon content of 0.2 wt.%≦Si≦2.0 wt.% results in particular in relatively uniformly distributed, dense particles of the quaternary α-Al(Fe,Mn)Si phase. These precipitated particles remove the iron and manganese from the solid solution without adversely affecting other properties such as corrosion behavior, i.e. electrolyte stability, or formability, thus increasing both the strength of the aluminum alloy and its electrical and thermal conductivity. A silicon content of less than 0.2 wt.% results in a reduction in the precipitation of the α-Al(Fe,Mn)Si phase, which, due to dissolved manganese, may reduce the electrical and thermal conductivity. Furthermore, the absence of the α-Al(Fe,Mn)Si phase has a negative effect on tool wear. The silicon content combined with magnesium may result in the formation of the Mg2Si phase or a metastable phase of the β-precipitation series. A silicon content of more than 0.3 wt.% may generate a sufficiently large phase fraction in combination with magnesium that a significant increase in strength can be realized by precipitation hardening. If the silicon content is too high, the solubility limit of Mg2Si is exceeded, so that no additional contribution to strength by precipitation hardening is made. Furthermore, there is an increased possibility of forming coarse Mg2Si phases that cannot be redissolved in a technically reasonable time during solution annealing and that may further reduce precipitation hardening as well as formability. Therefore, the silicon content is limited to 0.2 wt.%≦Si≦2 wt.%. In a preferred variant of the present aluminum alloy, the silicon content is limited to 0.2 wt.%≦Si≦1.5 wt.%, particularly preferably 0.3 wt.%≦Si≦1.3 wt.%, in order to allow ideal strength and rapid precipitation hardening.

[0021] The iron content of the aluminum alloy is at most 0.5% by weight. When combined with the specified amount of manganese content according to the invention, iron leads to the formation of the Al6(Mn,Fe) phase, and when combined with the specified amount of silicon content and manganese content according to the invention, as already explained above, leads to the precipitation of particles of the quaternary α-Al(Fe,Mn)Si phase. Iron in this case contributes to reducing the solubility of manganese in aluminum, so that more manganese is bound in intermetallic phases, which has a favorable effect on electrical and thermal conductivity. Furthermore, these intermetallic phases affect the recovery and recrystallization processes and improve the thermal stability of the mechanical properties. The interaction with silicon in the α-Al(Fe,Mn)Si or AlFeSi phases removes silicon from the solid solution, which can reduce the precipitation hardening. Above 0.5% by weight, iron can promote the formation of coarse intermetallic phases. The use of recycled aluminum products, which generally include the addition of iron, is furthermore desirable. Therefore, the aluminum alloy is preferably not iron-free, i.e. the iron content is greater than 0% by weight.

[0022] The copper content of the aluminum alloy is in the range of Cu≦0.8 wt%. In one embodiment of the aluminum alloy, the copper content of the aluminum alloy is in the range of Cu≦0.45 wt%, preferably 0.1 wt%≦Cu≦0.2 wt%. The fact that a copper content of up to 0.8 wt% is allowed results in an increased tolerance of the aluminum alloy to copper-containing aluminum alloy scrap, which facilitates the realization of a high proportion of recycled material in the manufacture of the battery housing. Overall, copper contributes to increasing strength. However, an excessively high copper content can adversely affect corrosion properties, so the copper content is limited to at most 0.6 wt%, preferably at most 0.45 wt%, in order to achieve improved electrolyte stability.

[0023] The manganese content of the aluminum alloy is at most 1.4% by weight. In addition to high corrosion resistance, a high manganese content of 1.0% to 1.4% by weight also provides high strength when combined with the silicon and iron contents in the specified amounts for the precipitation of particles of the quaternary α-Al(Fe,Mn)Si phase and Al6(Mn,Fe) phase in the highly cold-hardened state, e.g. H18 or H19. These intermetallic phases hinder the recovery and recrystallization processes and thus improve the thermal stability of the mechanical properties. A manganese content of more than 1.4% by weight promotes the formation of coarse intermetallic phases, which have an unfavorable effect on the forming properties in deep-draw forming processes. Furthermore, a manganese content of more than 1.4% by weight significantly reduces the electrical and thermal conductivity of the battery cell housing to such an extent that heat management becomes inefficient. A manganese content of at most 0.6% by weight reduces the increase in strength due to dispersoids and solid solution hardening. Due to the lower manganese content, more silicon is available for precipitation hardening, so in combination with a magnesium content of 0.2% to 1.5% by weight, increased strength due to precipitation hardening can be realized. This material combination achieved the highest yield strength values ​​in this study.

[0024] The magnesium content of the aluminum alloy is at most 2.0 wt%. In one embodiment of the battery cell housing, the magnesium content is at most 1.5 wt%, preferably 0.2 wt%≦Mg≦1.5 wt%. The fact that a maximum magnesium content of 2.0 wt% is permitted results in an increased tolerance of the aluminum alloy to magnesium-containing aluminum alloy scrap, such as UBC scrap, which further facilitates the realization of a high proportion of recycled material in the manufacture of the battery cell housing. Furthermore, the presence of magnesium above a content of at least 0.5 wt% results in efficient solid solution hardening, which contributes to an increase in cold hardening and therefore strength. Combined with silicon and with appropriate solution annealing and artificial aging, magnesium forms metastable precipitates of the β-precipitation series, which significantly increase the strength by precipitation hardening. However, since an excessively high magnesium content has a negative effect on the electrical and thermal conductivity, the magnesium content is limited according to the present invention to at most 2.0 wt%, preferably 1.5 wt%. To achieve improved mechanical properties, the magnesium content in one embodiment is set in the range 0.2 wt%≦Mg≦1.5 wt%, which represents a compromise between high strength, good forming behavior and high electrical and thermal conductivity combined with good recycling tolerance.

[0025] The chromium content of the aluminum alloy is in the range of Cr≦0.25 wt.%. In one embodiment of the battery cell housing according to the invention, the chromium content of the aluminum alloy is in the range of Cr≦0.15 wt.%, preferably Cr≦0.03 wt.%. The fact that a chromium content of up to 0.25 wt.% is allowed results in an increased tolerance of the aluminum alloy to chromium-containing aluminum alloy scrap, which facilitates the realization of a high proportion of recycled material in the manufacture of the battery cell housing. In addition, chromium also has a strength-increasing effect and forms dispersoids, which increase the thermal stability and prevent softening due to recrystallization or recovery. However, since an excessively high chromium content can adversely affect the electrical conductivity of the aluminum alloy, the chromium content is limited to 0.15 wt.%, preferably at most 0.03 wt.%, while the recycling tolerance and strength are still sufficient.

[0026] The zinc content of the aluminum alloy is in the range of Zn≦0.4 wt.%. In one embodiment of the battery cell housing, the zinc content of the aluminum alloy is at most 0.25 wt.%, preferably at most 0.1 wt.%. The fact that a zinc content of up to 0.4 wt.% is permitted results in an increased tolerance of the aluminum alloy to zinc-containing aluminum alloy scrap, which further facilitates the realization of a high recycling rate. Zinc also has a strength-increasing effect. However, an excessively high zinc content reduces the weldability, electrical and thermal conductivity, and corrosion resistance of the aluminum alloy, so the zinc content is limited to at most 0.4 wt.%. With a zinc content of at most 0.25 wt.%, preferably at most 0.1 wt.%, improved weldability and good electrolyte stability are achieved with the simultaneous contribution of zinc to strength increase.

[0027] The titanium content of the aluminum alloy is at most 0.2 wt%. In one embodiment of the battery cell housing, the titanium content of the aluminum alloy is in the range of 0.01 wt%≦Ti≦0.20 wt%, preferably 0.005 wt%≦Ti≦0.05 wt%. The fact that a titanium content of up to 0.20 wt% is permitted results in an increased tolerance of the aluminum alloy to titanium-containing aluminum alloy scrap, which facilitates the realization of a high proportion of recycled material in the manufacture of the battery cell housing. Titanium is used in small amounts for grain refinement when casting the aluminum alloy. However, an excessively high titanium content can adversely affect the forming properties of the aluminum alloy and significantly reduce the electrical and thermal conductivity, so the titanium content is limited to at most 0.2 wt% according to the present invention. Preferably, the titanium content is 0.01 wt%≦Ti≦0.20 wt%.

[0028] Vanadium is used in aluminum alloys to control recrystallization and grain refinement. Vanadium greatly reduces the electrical and thermal conductivity of aluminum both as an intermetallic phase and when dissolved, so the vanadium content of the aluminum alloy is limited to at most 0.05% by weight, preferably at most 0.03% by weight, and particularly preferably at most 0.0015% by weight. Higher vanadium contents reduce the conductivity to an extent that is incompatible with the desired increase in thermal management efficiency. Zirconium is also used in aluminum alloys to control recrystallization and grain refinement. However, the solubility of zirconium in aluminum is limited, so that an excessively high zirconium content causes the formation of coarse intermetallic phases that can reduce formability. Zirconium further reduces the electrical and thermal conductivity of aluminum, so that the zirconium content of the present aluminum alloy is limited to at most 0.25% by weight, preferably at most 0.2% by weight, preferably at most 0.05% by weight, particularly preferably at most 0.0015% by weight, A higher zirconium content reduces the conductivity to an extent that is incompatible with the desired increase in thermal management efficiency.

[0029] Nickel is used in aluminum alloys to increase thermal stability. However, nickel reduces the corrosion resistance of aluminum alloys and has limited availability. Therefore, the nickel content of the present aluminum alloy is limited to at most 0.2% by weight, preferably at most 0.05% by weight, and particularly preferably at most 0.03% by weight.

[0030] According to a further, particularly conductive, configuration of the battery cell housing, the aluminum alloy of the housing shell is hardenable and has the following content in weight percent: 0.3%≦Si≦0.7%, Fe≦0.5%, Cu≦0.45%, Mn≦0.10%, preferably ≦0.05%, 0.22%≦Mg≦0.8%, Cr≦0.03%, Zn≦0.1%, 0.01%≦Ti≦0.2%, V≦0.03%, preferably ≦0.015%, Zr≦0.05%, preferably ≦0.015%, Ni≦0.03%, preferably ≦0.015%, The balance is Al and incidental impurities each amounting to at most 0.03% and totaling at most 0.10%. The composition is

[0031] In this aluminum alloy, the magnesium content of 0.22% to 0.8% by weight is precisely matched with the silicon content of 0.3% to 0.7% by weight, which allows the aluminum alloy to have an effective precipitation hardening by metastable precipitation of the β precipitation series, thereby achieving a yield strength R of greater than 183 MPa in the tempered state T6 or T6x, for example. p0.2The iron content is at most 0.5% by weight, which contributes sufficiently to the thermal stability of the mechanical properties of the housing shell. The aluminum alloy of this configuration has a manganese content of at most 0.10% by weight, preferably at most 0.05% by weight, and can therefore be considered almost manganese-free. In this way, less quaternary α-Al(Fe,Mn)Si phase can be formed and more silicon can be made available for precipitation hardening. Furthermore, the adverse effect of manganese on electrical and thermal conductivity is limited. Due to the low alloy state, very high yield strengths in the tempered state T6 or T6x as well as particularly high electrical conductivity values ​​are achieved. With regard to the influence of the contents of chromium, zinc, titanium, vanadium, zirconium and nickel in this configuration, reference is made to the technical influences described above, which are also present in this configuration of the aluminum alloy.

[0032] Finally, the aluminum alloy of the housing shell according to a further configuration of the present battery cell housing is neither hardenable nor inherently hard and has the following composition by weight: 0.2%≦Si≦0.6%, Fe≦0.5%, Cu≦0.45%, 1.0%≦Mn≦1.4%, Mg≦1.10%, preferably ≦0.8%, Cr≦0.25%, Zn≦0.4%, Ti≦0.2%, preferably 0.01%≦Ti≦0.2%, V≦0.05%, Zr≦0.25%, Ni≦0.2%, The balance is Al and incidental impurities of not more than 0.05% individually and not more than 0.15% in total. The composition is

[0033] In this configuration of the aluminum alloy, the manganese content of 1.0% to at most 1.4% by weight, combined with the silicon and iron contents in the specified amounts, contributes to the precipitation of particles of the quaternary α-Al(Fe,Mn)Si phase as well as Al6(Mn,Fe) phase. These intermetallic phases impede the recovery and recrystallization processes, thus improving the thermal stability of the mechanical properties. In this configuration of the aluminum alloy, a yield strength R of 183 MPa is achieved with high to very high cold hardening (state H18 or state H19) by dispersoid and solid solution hardening. p0.2 Even higher values ​​of can be achieved.

[0034] According to a further configuration of the battery cell housing, in the case of the hardenable embodiment of the aluminum alloy, the housing shell has a temper state T6 or T6x, which has a very high yield strength R due to precipitation hardening. p0.2 The advantages of the battery cell housing made of an aluminum alloy in terms of weight, electrical conductivity and thermal conductivity of the battery cell housing are particularly high compared to battery cell housing made of steel.

[0035] If the housing shell according to the further configuration has at least one lid, which is connected to the housing shell by pressure fit and / or with a material, then for example a cup may be provided to receive the "jelly roll" of the circular battery cells, in which case the lid may provide the bottom of the cup. The lid may be manufactured by deep drawing and / or stretch drawing the cup from an aluminum alloy strip or by extrusion from an aluminum slug. A further material connection may be realized by soldering or welding between the housing shell and the lid, in which case the lid may be formed optionally as a separate part and also optionally from another material, for example another aluminum alloy or another metal. A pressure-fit connection between the housing shell and the lid may also be realized by crimping the lid to the housing shell. Finally, the battery cell housing may be closed with a further lid made of an aluminum alloy or another material after the jelly roll is placed in the cup-shaped housing shell. Again in this case a pressure fit and / or a material connection may be provided between the second lid and the housing shell.

[0036] According to a further aspect, the stated object is also realised for the use of an aluminium alloy for manufacturing a battery cell housing according to the invention, in which an aluminium alloy strip or sheet of the aluminium alloy is deep drawn and / or stretch drawn to form a tube or cup. Deep drawing and / or stretch drawing are economical processes for producing highly precise tubes or cups from an aluminium alloy strip or sheet. This use of the aluminium alloy is therefore particularly suitable for providing the battery cell housing according to the invention as a mass produced item.

[0037] According to an advantageous embodiment of the use, the aluminum alloy strip or sheet has the state H18, H19 before deep drawing and / or stretch drawing, in which case the highest yield strength R p0.2A value of at least 183 MPa in yield strength R may be achieved after deep drawing and / or stretch drawing of a tube or cup, and the battery cell housing according to the invention may also be manufactured from an aluminum alloy that is neither hardenable nor inherently hard. In this regard, even for large cell diameters, a yield strength R of at least 183 MPa in yield strength R of conventional aluminum alloys is not required. p0.2 A battery cell housing may be provided comprising an aluminum alloy according to the present invention that is neither hardenable nor inherently hard, having a value of

[0038] If the aluminium alloy strip or sheet, according to one configuration of the present use of the aluminium alloy strip, consists of a hardenable aluminium alloy, and the aluminium alloy strip has the state T4 before the deep drawing and / or stretch drawing, the deep drawing and / or stretch drawing may be accelerated and a greater degree of deformation may be produced. In that case, high values ​​of the yield strength of the battery cell housing according to the invention are achieved by hardening to the state T6 or T6x, for example by tempering at 205° C. for 30 minutes. In order to optimise the electrical and thermal conductivity, deliberate further ageing to the state T7 or T7x may also be envisaged, leading to a sufficiently high yield strength R of at least 183 MPa. p0.2 may be provided.

[0039] According to the alternative use of the present aluminum alloy strip or sheet, the housing shell of the present battery cell housing is manufactured by longitudinal seam welding a tube of aluminum alloy strip or sheet. Preferably, the tube is rolled from an aluminum alloy strip having a composition according to the present invention. In this case too, a particularly economical use of aluminum strip or sheet for manufacturing the battery cell housing according to the present invention may be provided.

[0040] Finally, according to the alternative use of aluminum alloys, the housing shell is extruded, optionally with a lid region, from an aluminum alloy slug. Alternatively, the housing shell of the battery cell housing may be manufactured by tube extrusion followed by optional tube drawing. Both methods represent the use of aluminum alloys that allow very economical manufacture of highly precise battery cell housings from aluminum alloys with advantageous properties in terms of thermal conductivity and weight.

[0041] The invention is explained in more detail below with reference to figures and exemplary embodiments. [Brief description of the drawings]

[0042] [Figure 1] FIG. 1 shows a schematic diagram of two different uses of aluminum alloys for manufacturing battery cell housings of circular battery cells. [Diagram 2] FIG. 1 shows a schematic diagram of a further use of an aluminum alloy for manufacturing a battery housing of a circular battery cell. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0043] The basis for these considerations is the known use of steel of type AISI 1020 to manufacture battery cell housings for battery cells. For example, large circular cells of type 4680 increase the requirements for the dissipation of heat from the interior of the circular battery cell, since the geometrically possible shapes of the circular battery cell are limited. The increase in cell height and, in particular, the cell diameter, results in a decrease in the surface area to volume ratio, which can greatly reduce the dissipation of heat. However, the use of aluminum alloys offers significantly better electrical and thermal conductivity than steel, so that the resulting reaction heat and ohmic heating can be dissipated more efficiently through the housing, and thus a performance gain can be expected, specifically through better thermal management. Moreover, since the housing in a cylindrical cell carries the current and constitutes one pole of the cell, the good electrical conductivity of aluminum reduces the generation of heat by lowering the ohmic resistance of the cell.

[0044] In contrast to this are the higher mechanical requirements on the battery cell housing of circular battery cells with diameters larger than 15 mm, especially larger than 20 mm or larger than 22 mm. To ensure this, a higher wall thickness of the battery cell housing, especially the housing shell, must be allowed. However, the higher wall thickness reduces the space for the "jelly roll", which leads to a shorter winding length and a smaller electrode area. Therefore, the loss or gain of the energy capacity of the battery cell housing can be estimated from the winding length ratio.

[0045] The thickness of the housing shell is calculated according to the Barlow equation, which is known from elastic statics.

[0046]

number

[0047] Here, σ φ : Stress component in the circumferential direction, p: Internal pressure, R i : inner radius, s: wall thickness, Using the standard stresses by Tresca,

[0048]

number

[0049] Using the condition,

[0050]

number

[0051] It can be designed with

[0052] In addition, the same maximum internal pressure,

[0053]

number

[0054] Assume that the cell has the same inner radius R i Assuming that,

[0055]

number

[0056] Therefore, the wall thickness ratio δ is calculated from the yield strength ratio as follows:

[0057]

number

[0058] It can be calculated as follows.

[0059] The wall thickness ratio δ to steel is a measure of the increase in wall thickness of the present battery cell housing when steel is replaced with aluminum, and may be used, in particular, to compare various aluminum alloy strips or sheets to one another.

[0060] For a given internal pressure, the minimum wall thickness can be determined for a battery cell housing of a circular battery cell made of steel of type AISI 1020, at which the aforementioned conditions can be met. Since cylindrical secondary batteries, in particular lithium-ion batteries, are usually equipped with a pressure relief mechanism that operates at, for example, 2 MPa, an internal pressure p = 9 MPa was calculated in the present case, taking into account a safety factor of 4.5, in order to provide a current interruption mechanism and a pressure relief mechanism and to reliably make a lateral rupture of the battery impossible. This represents a typical value for the required internal pressure stability. Using this minimum wall thickness of the housing shell together with the assumption of a constant size of the winding core and the defined thickness of the layers of the "jelly roll" of the battery, consisting of the separator, active material and current collector film, the winding length W of the "jelly roll" can be calculated as follows:

[0061]

number

[0062] Where: A: Area of ​​the winding surface, d jelly roll : The thickness of the film stack that wraps the jelly roll, W: Wrapping length, D battery : Outer diameter of battery cell housing, d shell : Thickness of the housing shell, i.e. wall thickness, D inner :Inner diameter of the winding surface.

[0063] The jellyroll film stack consists of a separator film, a cathode current collector film coated with a cathode active material, and an anode current collector film coated with an anode active material.

[0064] For a given outer diameter, the possible jelly roll winding length depending on the wall thickness of the battery cell housing determines the yield strength R of the housing shell. p0.2For various values ​​of , the capacity fade in a battery cell housing having a housing shell made at least partially of an aluminum alloy can be estimated by the winding length ratio.

[0065] For this purpose, the winding length ratio W Al / W steel can be calculated as follows:

[0066]

number

[0067] Where: d Al : Thickness of the housing shell when using each aluminum material d Steel :R p02、St = Thickness of the housing shell when receiving steel having a strength of 350 MPa.

[0068] In the case of a type 4680 circular cell having an outer diameter of the battery cell housing of 46 mm and a housing shell made of an aluminum alloy, the yield strength R p0.2 It has been found that the pressure must be at least 183 MPa, preferably at least 220 MPa, particularly preferably at least 250 MPa in order to keep the possible capacity fade below 5%. Thus, the battery cell housing according to the invention may provide advantages in terms of improved thermal management and reduced weight and acceptable capacity fade, especially in large circular battery cells having a diameter of more than 15 mm, preferably more than 20 mm or more than 22 mm.

[0069] Next, various aluminum alloys from different manufacturing processes were examined for suitability for providing battery cell housings, which are listed in Table 1. An exemplary embodiment according to the invention is designated E, and a comparative example not according to the invention is designated V.

[0070] [Table 1]

[0071] Table 2 provides information on the manufacturing methods for the various exemplary embodiments. In order to facilitate sampling for tensile testing compared to extruded tube samples, the exemplary embodiments investigated sometimes have a final thickness that is not suitable for battery cell housings, for example, Examples 6-10. The wall thickness of the housing shell of the battery cell housing of circular battery cells with a diameter larger than 15 mm, larger than 20 mm, preferably larger than 22 mm is preferably expected to be between 0.5 mm and 2.5 mm, preferably up to 1.5 mm, preferably 0.7 mm to 1.2 mm. In principle, wall thicknesses above 2.5 mm and below 0.5 mm can also be envisaged depending on the cell diameter, which is proportional to the stress component in the circumferential direction according to number 1.

[0072] However, despite the sometimes large difference (e.g., Examples 6 to 10) from the wall thickness required for the battery cell housing, the yield strength R p0.2 It is estimated that the measured value of the yield strength R can be easily realized by processing the present aluminum alloy to the final thickness to be realized in the aforementioned thickness range, particularly by adjusting the solution annealing and artificial aging. p0.2 Since R is independent of thickness and is determined by the composition and microstructure of the material, including the tempering state, the results determined in this study can be applied to any required wall thickness. p0.2 and R m All mechanical property values ​​refer to the values ​​according to DIN EN 6892.

[0073] [Table 2]

[0074] In Table 2, Examples 1-4 and Examples 10-14 were hot rolled and cold rolled from DC rolled ingot casts and homogenized under conventional conditions at final thickness. Homogenization was performed at temperatures between 480°C and 620°C for at least 0.5 hours. Hot rolling of the rolled ingots to form hot rolled strip was performed at temperatures between 280°C and 550°C, with the hot strip temperature after the last hot rolling pass being between 280°C and 380°C. The hot strip thickness, i.e., the thickness of the hot rolled strip, was between 2mm and 10mm. Cold rolling of the aluminum alloy strip or sheet may be performed in one or more passes.

[0075] Example 5 was produced by double roll casting followed by cold rolling with an intermediate anneal at 165°C after the first rolling pass of 15%. Examples 2, 3, 13 and 14 show exemplary embodiments according to the invention of the non-hardenable and non-intrinsically hard aluminum alloy for the battery cell housing, in particular the housing shell. Comparative Examples 1 and 4, not according to the invention, are similarly made of a non-hardenable and non-intrinsically hard aluminum alloy.

[0076] Exemplary embodiments 6-12 according to the invention comprise hardenable AlMgSi alloys. After hot rolling to final thickness and cold rolling or extrusion to final geometry, they were solution annealed and quenched to condition T4. These exemplary embodiments were then heat treated in the form of annealing or artificial aging to transform them to condition T6 or condition T6x, in this study to condition T64, by additional 2% elongation. Transformation to condition T7 or T7x is also contemplated in this study. The achievable yield strength values ​​R for examples made of different aluminum alloys and manufactured with different process steps are shown. p0.2 was measured and used to calculate the wall thickness or wrap length ratio compared to a battery cell housing made of AISI 1020 steel.

[0077] Furthermore, the electrical conductivity in MS / m and (%IACS) was determined for various materials by eddy current testing according to DIN EN 2004-1 1993-09. The thermal conductivity λ is given by the Wiedemann-Franz law:

[0078]

number

[0079] Where: L=2.00 10 -8 WΩK -2 ("The Lorentz Number of Aluminum at Room Temperature", Aluminum Handbook Vol. 1, 16th Edition (Aluminum Verlag) σ: Electrical conductivity, T: temperature (room temperature is assumed to be 25°C), It can be calculated with the help of electrical conductivity σ, taking into account

[0080] For the reference material AISI 1020 steel, the thermal conductivity is about 67 W / mK at room temperature. The results of the calculations are shown in Table 3. All aluminum alloys are predicted to be well above the reference values ​​for type AISI 1020 steel for electrical and thermal conductivity. On the other hand, comparative example 1 shows an insufficient yield strength of 100 MPa, resulting in an outer diameter / wall thickness ratio of 23.71 at the assumed internal pressure of 9 MPa. The wall thickness required for the battery cell housing obtained therefrom, for example type 4680 with an outer diameter of 46 mm, would result in a significant capacity drop in relation to the feasible winding length of the jelly roll, so that the advantages of the excellent electrical and thermal conductivity cannot be utilized. On the other hand, exemplary embodiments 2 and 3 according to the invention show a significantly smaller drop with respect to the winding length. Exemplary embodiments 2 and 3 still have acceptable electrical and thermal conductivity. Due to the large difference in these parameters with material AISI 1020 steel, suitability for large battery cell housings can still be envisaged.

[0081] Comparative Example 4, which represents the material AA3003 H14 often used for prismatic battery boxes, also had insufficient yield strength R p0.2 , which would result in a significant reduction in winding length considering the required wall thickness, so the comparative example in condition H14 is not suitable for the battery cell housing according to the present invention. Exemplary embodiment 13 has almost the same aluminum alloy as comparative example 4 due to the different material condition H19. However, due to the good processing properties of this aluminum alloy, a battery cell housing with a small reduction in winding length can also be manufactured.

[0082] Exemplary embodiments 5-9 according to the present invention exhibit consistently high strength, with exemplary embodiment 5 in condition H19 produced by double roll casting and cold rolling with a subsequent 15% first rolling pass followed by an intermediate anneal at 165°C, and exemplary embodiments 6-9 produced by extrusion. The extruded variants were measured in condition T6. The strength enhancing properties of copper compared to the addition of zirconium can be clearly seen from a comparison of exemplary embodiment 6 with exemplary embodiment 7. Nickel also exhibits a yield strength R as shown in exemplary embodiment 9. p0.2 This results in an increase in.

[0083] The highest yield strength values ​​were obtained for the exemplary embodiment 10, which was produced using a DC ingot casting route with hot and cold rolling and solution annealing in a continuous furnace. In this study, the transformation to condition T6 was performed by coil annealing at 180° C. for 4 hours. The smallest wrap length loss of less than 1.5% was achieved for the aluminum alloy strip according to the exemplary embodiment 10. The lower strength aluminum alloy variants of the exemplary embodiments 11 and 12 cover the group of aluminum alloys AlMgSi, exemplary embodiments 5 to 12, showing that these aluminum alloys are also suitable for producing battery cell housings according to the present invention.

[0084] Due to the different processing characteristics of the present aluminum alloy, there are various possible uses of the present aluminum alloy for manufacturing the present battery cell housing, which are described in more detail below with the aid of the drawings.

[0085] 1 now shows three different uses of aluminum alloys for manufacturing battery cell housings. Firstly, an aluminum alloy strip 1 is shown which can be produced by casting an ingot for rolling, for example by the DC casting method or by the cast-rolling method followed by hot and / or cold rolling. A segment 2 produced from the strip 1 is drawn in a deep-drawing and / or stretch-drawing tool (not shown) to form a tube, in particular a cylindrical cup 3 into which a "jelly roll" (not shown) can be inserted.

[0086] According to a further illustrated use, the aluminum alloy strip is formed, for example by roll forming and subsequent welding, into a longitudinally seam welded tube 4. The housing shell of the battery cell housing may then be separated therefrom as a tube section 5. The tube section 5 may also be provided with a lid 6 to subsequently accommodate a "jelly roll". The lid 6 is connected to the tube or tube section 5 by means of a material connection or a press-fit connection, for example by soldering, welding or crimping.

[0087] A third use involves the production of extruded tubes 7, which are typically drawn to size. The tube sections 5 may then likewise be provided with caps 6.

[0088] Finally, Figure 2 shows, in a schematic way, the use of the aluminium alloy to manufacture a battery cell housing by extruding an aluminium alloy slug 8 in an extrusion press 9 with a punch 10 and a die 11. The finished housing shell 12 with lid is highly precise and can be produced as a mass-produced commodity as well. Nevertheless, tube sections can also be easily produced by extrusion, i.e. without a lid. The processing of the tube section 5 to form the battery cell housing for circular cells is described with reference to Figure 1.

[0089] [Table 3]

Claims

1. A battery cell housing for a circular battery cell, comprising a cylindrical housing shell having an outer diameter of more than 15 mm, preferably more than 20 mm, particularly preferably more than 22 mm, said housing shell at least partially made of an aluminum alloy, said housing shell having a yield strength R p0.2 is at least 183 MPa, preferably at least 220 MPa, particularly preferably at least 250 MPa.

2. 2. The battery cell housing according to claim 1, characterized in that the housing shell of the battery cell housing has a wall thickness that satisfies the following relationship: outer diameter / wall thickness > 41.5, preferably > 47.5, particularly preferably > 55.

0.

3. 3. The battery cell housing according to claim 1 or 2, characterized in that the housing shell has an electrical conductivity of more than 25 MS / m, preferably more than 28 MS / m, particularly preferably more than 30 MS / m.

4. The at least one aluminum alloy of the housing shell comprises, in weight percent, 0.2%≦Si≦2.0%, Fe≦0.5%, Cu≦0.8%, Mn≦1.4%, Mg≦2.0%, Cr≦0.25%, Zn≦0.4%, Ti≦0.2%, V≦0.05%, Zr≦0.25%, Ni≦0.2%, The balance is Al and incidental impurities individually at most 0.05% and in total at most 0.15%. The battery cell housing according to any one of claims 1 to 3, characterized in that it has a composition.

5. The aluminum alloy of the housing shell comprises, in weight percent, 0.2%≦Si≦1.5%, preferably 0.3%≦Si≦1.3%, Fe≦0.5%, Cu≦0.6%, preferably ≦0.45%, Mn≦1.4%, preferably 1.0%≦Mn≦1.4%, more preferably Mn≦0.6%, Mg≦1.5%, preferably 0.2%≦Mg≦1.5%, Cr≦0.25%, preferably ≦0.15%, Zn≦0.25%, 0.01%≦Ti≦0.20%, V≦0.05%, preferably ≦0.03%, Zr≦0.20%, preferably ≦0.05%, Ni≦0.05%, preferably ≦0.03%, The balance is Al and inevitable impurities individually at most 0.05%, preferably at most 0.03%, and in total at most 0.15%, preferably at most 0.10%. The battery cell housing according to any one of claims 1 to 4, characterized in that it has a composition.

6. The aluminum alloy of the housing shell is hardenable and has the following composition by weight: 0.3%≦Si≦0.7%, Fe≦0.5%, Cu≦0.45%, Mn≦0.05%, 0.22%≦Mg≦0.8%, Cr≦0.03%, Zn≦0.1%, 0.01%≦Ti≦0.20%, V≦0.03%, preferably ≦0.015%, Zr≦0.05%, preferably ≦0.015%, Ni≦0.03%, preferably ≦0.015%, The balance is Al and unavoidable impurities individually at most 0.03% and in total at most 0.10%. The battery cell housing according to any one of claims 1 to 4, characterized in that it has a composition.

7. The aluminum alloy of the housing shell is non-hardenable and has the following composition by weight percent: 0.2%≦Si≦0.6%, Fe≦0.5%, Cu≦0.45%, 1.0%≦Mn≦1.4%, Mg≦1.10%, preferably ≦0.8%, Cr≦0.25%, Zn≦0.4%, Ti≦0.2%, preferably 0.01%≦Ti≦0.20%, V≦0.05%, Zr≦0.25%, Ni≦0.2%, The balance is Al and incidental impurities individually at most 0.05% and in total at most 0.15%. The battery cell housing according to any one of claims 1 to 4, characterized in that it has a composition.

8. 8. The battery cell housing according to claim 1, wherein the housing shell is made of a hardenable alloy and has a temper state T6, T6x, T7 or T7x.

9. 4. The battery cell housing according to claim 1, wherein the housing shell has at least one lid connected thereto by material or by force fit.

10. Use of an aluminium alloy for manufacturing a battery cell housing according to any one of claims 1 to 9, characterised in that an aluminium alloy strip or sheet of the aluminium alloy is deep drawn and / or stretch drawn to form a tube or cup.

11. 11. Use according to claim 10, characterised in that the aluminium alloy strip or sheet is in state H18, H19 before the deep drawing and / or draw drawing.

12. 12. Use according to claim 10 or 11, characterised in that the aluminium alloy strip or sheet consists of a hardenable aluminium alloy and has a condition T4 before the deep drawing and / or draw drawing.

13. Use according to any one of claims 10 to 12, characterized in that the housing shell of the battery cell housing is alternatively manufactured by longitudinal seam welding of a tube of optionally rolled aluminium alloy strip or sheet.

14. 11. Use according to claim 10, characterized in that the housing shell is alternatively extruded, optionally with a lid region from an aluminium alloy slug, or the housing shell is drawn from an extruded tube.

Citation Information

Patent Citations

  • High-strength aluminum alloy used for lithium ion battery shell and having excellent laser welding performance

    CN103981401A

  • Aluminum alloy profile for power battery shell as well as processing technology and application of aluminum alloy profile

    CN113373348A

  • Method for producing aluminum alloy sheet for secondary battery case

    JP2002339049A

  • Aluminum alloy sheet for case of secondary battery

    JP2003034833A

  • Aluminum alloy plate for battery case of rectangular section

    JP2004197172A